Quick Reference Guide for Plant Growth Regulators (PGR) in Florida Citrus Production - Tripti Vashisth; Jamie D. Burrow (EDIS)
This 2-page fact sheet is a minor revision written by Tripti Vashisth and Jamie D. Burrow, and published by the Horticultural Sciences Department, July 2019.